An upstream promoter element of the Acanthamoeba castellanii TBP gene binds a DNA sequence specific transcription activating protein, TPBF. - Liu, F (1993)
We have characterized a positive-acting element in the upstream portion of the Acanthamoeba TBP gene promoter. The 27 bp element (TPE), located within the promoter between -97 and -70, stimulates transcription in an orientation independent fashion and tolerates modest changes in its distance from the TATA box. The TPE does not, however, function synergistically nor when positioned 3000 bp 5' or 260 base pairs 3' of the transcription start site. The TPE binds a DNA sequence-dependent factor, TPBF, which we have partly purified. TPBF was characterized using in vitro transcription, DNase I footprinting, methylation interference and electrophoretic mobility shift assays. TPBF does not have a counterpart in HeLa cells, but nonetheless strongly stimulates transcription of the Acanthamoeba TBP gene in mammalian extracts. Our results also suggest that there are additional positively and negatively acting elements within the TBP gene promoter, for which a model is presented.